INFLUENCE OF TECHNOLOGICAL PARAMETERS OF PROCESS OF PORTAGE OF CONCRETE MIXTURESON PIPELINES ON THE PRODUCTIVITY OF SOLUTIONA CONCRETE PUMPS (CONCRETE PUMPS) - Емельянова, И. А.; Задорожный, А. А.; Меленцов, Н. А. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The analysis of process of motion of concrete mixture is executed on a pipeline and dependence is offered for determination of the productivity of solution is a concrete pump(concrete pumps). Calculation data over of technological parameters of process of portage of concrete mixtures are brought taking into account the productivity of machines and diameters of pipelines. Keywords: concrete pump, concrete mixture, transport pipeline, middle speed, viscidity, mobility.